2010
DOI: 10.3748/wjg.v16.i30.3853
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated endocrine carcinoma of the pancreas responded to gemcitabine: Case report

Abstract: Poorly differentiated endocrine carcinoma (PDEC) of the pancreas is a rare and aggressive tumor. First-line treatment is commonly a combination of etoposide and cisplatin, but there is no consensus regarding further treatment recommendations. In this report, we describe a case of pancreatic PDEC treated with gemcitabine as third-line chemotherapy. A 62-year-old man with pancreatic PDEC was administered etoposide plus cisplatin as first-line treatment; he then received irinotecan for tumor relapse. However, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…All of the studies concurringly found Gemcitabine to be well tolerated, with a favorable side-effects profile [ 33 , 34 , 35 ]. Concerning pNEC in particular, data are currently lacking; however, several case-reports observed a response and satisfactory tolerability to treatment with Gemcitabine as a salvage therapy [ 36 ], third-line therapy [ 37 ] or in combination with S-1 [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies concurringly found Gemcitabine to be well tolerated, with a favorable side-effects profile [ 33 , 34 , 35 ]. Concerning pNEC in particular, data are currently lacking; however, several case-reports observed a response and satisfactory tolerability to treatment with Gemcitabine as a salvage therapy [ 36 ], third-line therapy [ 37 ] or in combination with S-1 [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MRTF-A and –B promoted pancreatic cancer growth in a nude mouse assay, and high expression of MRTFs in pancreatic cancer cell lines is associated with resistance to the chemotherapeutic agent gemcitabine [ 39 ]. Alteration towards a more stem cell-like phenotype and increased drug resistance is meaningful since less differentiated tumours tend to be more aggressive and typically respond poorly to traditional chemotherapeutics [ 40 ].…”
Section: Myocardin-related Transcription Factor (Mrtf) Familymentioning
confidence: 99%